Development phase of mobile numerical application for children with autism: Math4Autism - Aziz, N.S.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
The use of mobile devices in teaching and learning has intensified in this era of information and communication technology. The utilization of mobile learning application created learning beyond the boundaries of four wall of the traditional classrooms. The mobile learning application can be used everywhere at any time. This fits the restraint of the children with autism. The development lifecycle used to develop the working prototype, was adapted from ADDIE lifecycle which consists of five phases; analysis, design, development, implementation and evaluation. This paper objectively presents the development phase of the Math4Autism development lifecycle. Math4Autism is a prototype of mobile learning application developed for the children with Autism to learn basic numbers, basic shapes and sizes. This paper discusses the tools used in developing the working prototype and presents the menu hierarchy for the prototype. The working prototype was tested to ensure its functionality works and free from errors. The result shows that the working prototype is ready to be tested to the real users. Â© 2016 IEEE.